Conceptual Quantum Chemical Analysis of Bonding and Noncovalent Interactions in the Formation of Frustrated Lewis Pairs. Issue 14 (18th February 2015) - Skara, Gabriella; Pinter, Balazs; Top, Jens; Geerlings, Paul; De Proft, Frank; De Vleeschouwer, Freija
Abstract The contributions of covalent and noncovalent interactions to the formation of classical adducts of bulky Lewis acids and bases and frustrated Lewis pairs (FLPs) were scrutinized by using various conceptual quantum chemical techniques. Significantly negative complexation energies were calculated for fourteen investigated Lewis pairs containing bases and acids with substituents of various sizes. A Ziegler–Rauk‐type energy decomposition analysis confirmed that two types of Lewis pairs can be distinguished on the basis of the nature of the primary interactions between reactants; dative‐bond formation and concomitant charge transfer from the Lewis base to the acid is the dominant and most stabilizing factor in the formation of Lewis acid–base adducts, whereas weak interactions are the main thermodynamic driving force (>50 %) for FLPs. Moreover, the ease and extent of structural deformation of the monomers appears to be a key component in the formation of the former type of Lewis pairs. A Natural Orbital for Chemical Valence (NOCV) analysis, which was used to visualize and quantify the charge transfer between the base and the acid, clearly showed the importance and lack of this type of interaction for adducts and FLPs, respectively. The Noncovalent Interaction (NCI) method revealed several kinds of weak interactions between the acid and base components, such as dispersion, π–π stacking, CH⋅⋅⋅π interaction, weak hydrogen bonding, halogen bonding, and weak acid–base interactions, whereas the Quantum Theory of Atoms in Molecules (QTAIM) provided further conceptual insight into strong acid–base interactions.